Enhancing Feedback on Professionalism and Communication Skills in Anesthesia Residency Programs. (August 2017) - Mitchell, John D.; Ku, Cindy; Diachun, Carol Ann B.; DiLorenzo, Amy; Lee, Daniel E.; Karan, Suzanne; Wong, Vanessa; Schell, Randall M.; Brzezinski, Marek; Jones, Stephanie B.
Abstract : BACKGROUND: Despite its importance, training faculty to provide feedback to residents remains challenging. We hypothesized that, overall, at 4 institutions, a faculty development program on providing feedback on professionalism and communication skills would lead to (1) an improvement in the quantity, quality, and utility of feedback and (2) an increase in feedback containing negative/constructive feedback and pertaining to professionalism/communication. As secondary analyses, we explored these outcomes at the individual institutions. METHODS: In this prospective cohort study (October 2013 to July 2014), we implemented a video-based educational program on feedback at 4 institutions. Feedback records from 3 months before to 3 months after the intervention were rated for quality (0–5), utility (0–5), and whether they had negative/constructive feedback and/or were related to professionalism/communication. Feedback records during the preintervention, intervention, and postintervention periods were compared using the Kruskal-Wallis and χ 2 tests. Data are reported as median (interquartile range) or proportion/percentage. RESULTS: A total of 1926 feedback records were rated. The institutions overall did not have a significant difference in feedback quantity (preintervention: 855/3046 [28.1%]; postintervention: 896/3327 [26.9%]; odds ratio: 1.06; 95% confidence interval, 0.95–1.18; P = .31), feedback quality (preintervention: 2 [1–4]; intervention: 2 [1–4]; postintervention: 2 [1–4]; P = .90), feedback utility (preintervention: 1 [1–3]; intervention: 2 [1–3]; postintervention: 1 [1–2]; P = .61), or percentage of feedback records containing negative/constructive feedback (preintervention: 27%; intervention: 32%; postintervention: 25%; P = .12) or related to professionalism/communication (preintervention: 23%; intervention: 33%; postintervention: 24%; P = .03). Institution 1 had a significant difference in feedback quality (preintervention: 2 [1–3]; intervention: 3 [2–4]; postintervention: 3 [2–4]; P = .001) and utility (preintervention: 1 [1–3]; intervention: 2 [1–3]; postintervention: 2 [1–4]; P = .008). Institution 3 had a significant difference in the percentage of feedback records containing negative/constructive feedback (preintervention: 16%; intervention: 28%; postintervention: 17%; P = .02). Institution 2 had a significant difference in the percentage of feedback records related to professionalism/communication (preintervention: 26%; intervention: 57%; postintervention: 31%; P < .001). CONCLUSIONS: We detected no overall changes but did detect different changes at each institution despite the identical intervention. The intervention may be more effective with new faculty and/or smaller discussion sessions. Future steps include refining the rating system, exploring ways to sustain changes, and investigating other factors contributing to feedback quality and utility. Abstract : Supplemental Digital Content is available in the text.Published ahead of print June 7, 2017.